Phase Two Wins With Own Tune - Unknown (Daily Express)
For the first time ever, a steelband has won a Panorama competition with its own composition. The unsponsored Phase II Pan Groove with their rendition of "I Like to Beat Pan" composed and arranged by Lennox "Boogsie" Sharpe with lyrics by Alvin Daniel beat the much favoured WITCO Gay Desperadoes into second place.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Calypso (Music) -- Trinidad and Tobago; Panorama (Musical festival); Calypso musicians -- Trinidad and Tobago